(untitled) (Scientific journal of the Fergana State University, 2025)
Global climate change is having a significant impact on water and water resources across the globe, manifesting itself in the availability, quality and distribution of this water. Changing climate patterns, i.e. changes in precipitation, temperature increases and extreme weather events, disrupt the hydrological cycle and pose a number of challenges to water resource management. These impacts are wide-ranging and diverse, affecting ecosystems, agriculture, human health and economic development. In order to adapt to these changes and ensure sustainable water resource management and mitigate the risk of water scarcity, several reservoirs have been built in the Middle Zarafshan Basin. The most important of them are the Kattakurgan and Akdarya reservoirs. There are small reservoirs such as Tusinsay, Koratepa, Sobirsay and low-pressure reservoirs such as Omondara and Muminabad. The importance of these reservoirs in the Middle Zarafshan basin in the national economy is considered to be very great. This article extensively covers the impact of the reservoirs located in the basin on the environment, the formation of flooded and inundated areas, the impact on the population and national economy objects affected by the reservoir. Also, the long-term water consumption and inflow of the Kattakurgan and Akdarya reservoirs are analyzed.